Landscape of Indian Legal Research - Ashish Srivastava (Krytyka Prawa, 2024)
Francis Bacon says knowledge is power. The creation of knowledge and its dissemina-tion largely depends on the creation of literary works. The great works of Shakespeare, da Vinci, Homer, Picasso, Milton, Tagore etc. have been a treasure trove of mankind. Human beings have enjoyed the work, been inspired by the work, taken joy and eternal bliss in such works. However, the creation of knowledge is dependent on pre-existing knowledge. Creators create a work which requires hard work, imagi-nation, creativity and which is incentivised by recognition of their work. The legal order of a couth society affords protection to such a work by copyright law & fair use. Fair use allows a person to use a work by duly acknowledging and referencing the work. Issue of plagiarism and abuse of fair use was aggravated by human greed. The economic implication of copyright infringement aggravated the whole issue. Referencing turned into war. The Bluebook, the Maroonbook, the ALWD, the APA and OSCOLA citation styles engaged in some kind of a war. Reference management systems like Zotero, Endnote, Mendeley etc. just fanned the flame. Disruptive and generative artificial intelligence has created a serious challenge to academic research. In this paper, the author attempts to delve into the inter-linkage of academic writing, research, citation, copyright, referencing mechanism and plagiarism in contempo-rary society, and the aftermath of it. The author attempts to investigate the challenges of writing and the protection of works vis-a-vis referencing tools and techniques